Secrets of becoming : negotiating Whitehead, Deleuze, and Butler - Faber, Roland, 1960-; Stephenson, Andrea M. (Fordham University Press, 2011)
"This collection of essays brings together three very different thinkers around their shared immanentism and anti-substantialism, attending to the differing ways that events, bodies, and gods become in the absence of a transcendent order of being. Operating without a form, essence, or original according to which becoming comes to be, Whitehead, Deleuze, and Butler share an attentiveness to that which has never been before. This volume promises a kind of newness at all levels: it stages an unprecedented conversation among thinkers committed to the unprecedented."--Mary Jane Rubenstein. Wesleyan University.